Derivation and validation of SIDIAP-FHP score: A new risk model predicting cardiovascular disease in familial hypercholesterolemia phenotype. (January 2020) - Ramos, Rafel; Masana, Luís; Comas-Cufí, Marc; García-Gil, Maria; Martí-Lluch, Ruth; Ponjoan, Anna; Plana, Núria; Alves-Cabratosa, Lia; Marrugat, Jaume; Elosua, Roberto; Dégano, Irene R.; Gomez-Marcos, Mauel A.; et al.
Abstract: Background and aims: Assessment of individual cardiovascular risk, distinguishing primary and secondary prevention, would improve the clinical management of the population with familial hypercholesterolemia. We aimed to develop and validate two risk functions to predict incident and recurrent atherosclerotic cardiovascular disease (ASCVD) in a primary care-based population with familial hypercholesterolemia phenotype (FHP), and to compare their predictive capacity with that of the SpAnish Familial hypErcHolEsterolemiA cohoRT (SAFEHEART) risk equation (SAFEHEART-RE). Methods: Data from the Catalan primary care system database (SIDIAP) of patients ≥18 years old with FHP in 2006–2013 were used to develop and validate two risk functions to predict incident and recurrent ASCVD. A validation dataset was also used to compare the model predictive capacity to that of SAFEHEART-RE. Results: The new model (SIDIAP-FHP) included age, diabetes, smoking, sex (male), hypertension, and baseline low-density lipoprotein cholesterol in the primary prevention cohort and age, diabetes, smoking, and disease characteristics (progressive, recent, polyvascular, or included myocardial infarction) in the secondary prevention cohort. The models demonstrated a fair fit: C-Statistic: 0.71 (95%CI:0.68–0.75) in primary prevention and 0.65 (95%CI:0.60–0.70) in secondary prevention (higher than that of SAFEHEART-RE: 0.64 [95%CI:0.60–0.68] and 0.55 [95%CI:0.51–0.59], respectively; both p < 0.01). The Brier scores obtained with the SIDIAP-FHP score were significantly lower than that obtained with SAFEHEART-RE in both the primary and secondary prevention cohorts. Conclusions: The SIDIAP-FHP score provides accurate ASCVD risk estimates for primary and secondary prevention in the FHP population, with better predictive capacity than that of SAFEHEART-RE in this general population, especially in persons with previous ASCVD. Graphical abstract: Image 1 Highlights: Familial hypercholesterolemia phenotype entails high risk of atherosclerotic events. A patient-tailored assessment of risk may help achieve optimal treatment. The SIDIAP-FHP score is useful in general population or primary care settings. Clinicians may use the SIDIAP-FHP to prioritize referrals to lipids-clinic specialists.